PERAN GURU MENGIMPLEMENTASI SIKAP MODERASI BERAGAMA DI SEKOLAH - Bastian, Gloria Sitania (Institut Agama Kristen Negeri (IAKN) Ambon, 2022)
The objectives of this study are (1). to explain the role of teachers in implementing religious moderation as a harmonious and peace-loving school, (2) to find out the teacher's strategy in implementing religious moderation as a harmonious and peace-loving school. The research method used is a qualitative descriptive approach. The results showed that (1) The implementation of religious moderation values in West Seram State Senior High School is very relevant to be given at an early age, namely to children (students) of West Seram State Senior High School. Such as attitudes of tolerance, attitudes of justice, attitudes of balance, and equality so that the next generation can maintain the integrity of the nation. Therefore, students are expected to have tolerance among others. With a culture of tolerance that becomes the lifestyle of a pluralistic society, conflict can be prevented before it occurs and can also be resolved or repaired if it has occurred. With the awareness of tolerance built on the basis of the law of love, peace between people in religious moderation is realized. In essence, religious moderation from the perspective of the law of love creates awareness to harmonize relations between religions, increase the sense of nationality and positive constructs. Moderation based on the law of love will strengthen unity and integrity in pluralism, (2) In actualizing the concept of religious moderation in the context of a multicultural society that makes educational institutions a laboratory base for religious moderation. Educational institutions are very appropriate to be a laboratory of religious moderation. As has been understood that Indonesia is a nation that has a variety of ethnicities and religions. Indonesia has unique characteristics, but is full of challenges.Keywords: Implementation of Attitudes, Religious Moderation, High School